Corporate social performance : reflecting on the past and investing in the future - Stachowicz-Stanusch, Agata (Emerald Publishing Limited : IAP - Information Age Publishing Inc., 2017)
Corporate Social Performance - reflecting on the past and investing in the future is aimed at filling the fundamental gap that exists in our understanding of the drivers Corporate Social Performance, its evolution and relationships with the existing concepts and theories and the paradoxes that come from those connections. Moreover the volume aims at shedding the light on most important pitfalls that may occur while CSP application in business practice. The last but not least reason for its publishing is to show Corporate Social Performance as a significant pathway to the better world, that, as I hope, will be the inspiration for the readers.This book is authored by a range of international experts and scientists from all over the world with a diversity of professional and cultural backgrounds what hopefully will give the readers the opportunity to understand the CSP concept from different perspectives.
Keywords: Social responsibility of business.; Corporations -- Moral and ethical aspects.; Corporate governance -- Social aspects.; Business & Economics -- Business Ethics.; Business ethics and social responsibility.; elektronické knihy; electronic books